PENGARUH PEMAHAMAN KONSEP DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP KEMAMPUAN PENYELESAIAN SOAL MATEMATIKA BERBASIS HIGHER ORDER THINKING SKILL PADA SISWA SEKOLAH DASAR - Iin Wustha Mutmainnah; Irwan Akib; St. Fithriani Saleh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of conceptual understanding and critical thinking skills on the ability to solve mathematics problems based on higher order thinking skills in elementary school students. The study was conducted in elementary school cluster 20, Liliriaja District, Soppeng Regency, which consists of 10 schools. The population in this study were fifth-grade students in elementary school cluster 20. Through stratified cluster sampling techniques, researchers determined 5 schools as research samples totaling 51 students. Data collection was carried out through test techniques and analyzed through regression tests using SPSS. Based on the results of the study, conceptual understanding and critical thinking skills have a significant effect on the ability to solve mathematics problems based on higher order thinking skills in elementary school students. Keywords: conceptual understanding, critical thinking skills, HOTS